The Reform of the Fund. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1969)
This paper discusses some events that led to beginning of the IMF reform. At the Twenty-Second Annual Meeting of the Board of Governors at Rio de Janeiro in September 1967, certain Governors urged that proposals for the amendment of the Articles to establish the special drawing rights facility must be accompanied by other proposals that became known as proposals to reform the IMF. The Board of Governors adopted a Resolution at Rio de Janeiro in which the Executive Directors were requested to proceed with their work relating to the proposed facility, on the basis of the Outline attached to the Resolution, and also improvements in the present rules and practices of the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet